Application of models and methods of integrated risk management of stakeholders of scientific projects in conditions of uncertainty and behavioral economics - Bedrii, Dmytro; Danchenko, Elena; Semko, Inga (Technology audit and production reserves, 2020)
The object of research is the processes of integrated risk management of stakeholders of scientific projects, including the project team, the main executors of the project (scientists) and other stakeholders, in conditions of uncertainty and behavioral economics. Today, scientists work in difficult conditions of uncertainty about the prospects for the development of science, technology and engineering. Therefore, it can lead to personnel risks, conflicts and behavioral economics and have a negative impact on the planning and implementation of scientific projects. The main hypothesis of the study is the assumption that the success of scientific projects depends on the effective management of their stakeholders in order to achieve their goals. It is necessary to systematically approach the analysis of stakeholders of scientific projects, the use of integrated risk management of stakeholders of scientific projects in conditions of uncertainty and behavioral economics. Based on the analysis of risk management methods in different areas of activity and taking into account the conceptual model of integrated risk management of scientific projects, a method of integrated risk management of stakeholders of scientific projects in uncertainty and behavioral economics was proposed. For the practical application of the developed models and methods of integrated risk management of stakeholders of scientific projects in conditions of uncertainty and behavioral economics, the scientific project was considered. Their use, even at the stage of initiating scientific projects, allowed the project manager and his/her team to calculate the indicator of «toxicity» for each alternative stakeholders and compare them with each other. It is based on data obtained in the process of assessing personnel risks, conflicts and factors of behavioral economics, which was conducted using the method of expert assessments. The indicator of «toxicity» is limited and should be close to zero. An example of choosing a stakeholder for the supply of stationery is considered. This result allowed to increase the efficiency of inclusion of stakeholders in the participants of the scientific project.